2016
DOI: 10.13075/ijomeh.1896.00546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of atmospheric pressure in different seasons on blood pressure in patients with arterial hypertension

Abstract: Objectives: Atmospheric pressure is the most objective weather factor because regardless of if outdoors or indoors it affects all objects in the same way. The majority of previous studies have used the average daily values of atmospheric pressure in a bioclimatic analysis and have found no correlation with blood pressure changes. The main objective of our research was to assess the relationship between atmospheric pressure recorded with a frequency of 1 measurement per minute and the results of 24-h blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…BP is affected by various measurement conditions such as room temperature, atmospheric pressure, weather changes, and temperature variability, as well as outside temperature. Hours of daylight and the availability of air conditioning or heating are also associated with the amplitude of seasonal variation in BP.…”
Section: Discussionmentioning
confidence: 99%
“…BP is affected by various measurement conditions such as room temperature, atmospheric pressure, weather changes, and temperature variability, as well as outside temperature. Hours of daylight and the availability of air conditioning or heating are also associated with the amplitude of seasonal variation in BP.…”
Section: Discussionmentioning
confidence: 99%
“…A negative effect of low BP on blood pressure levels was also reported in hypertensive patients who did not respond to treatment [6]. A significant inverse relationship between atmospheric pressure and blood pressure during the spring days, and only for systolic blood pressure, during winter nights, was observed in Poland [7].…”
Section: Discussionmentioning
confidence: 80%
“…BP in the biosynoptic analysis seems to be the most objective meteorological factor having the same influence on us-indoors and outdoors. The decrease in BP reduces blood oxygenation and pulse rate [5], is associated with a higher blood pressure [6,7], and associated with a higher risk of adverse cardiovascular events [8,9]. We failed to find any experiment-based studies in the effect of relative humidity or wind speed on human physiological indices.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies of falls have scarcely addressed the role of atmospheric pressure, and only a few reported that atmospheric pressure has an effect on the incidence of hip fractures and trauma admissions [ 19 , 20 ]. However, it is known that low atmospheric pressure can cause headaches, a feeling of dizziness and decreases in blood pressure among weather-sensitive people [ 47 , 48 , 49 ]. The association between dizziness and falls among middle-aged adults was found by Peeters et al [ 50 ] during the analysis of data from population-based cohort studies in Australia and the UK.…”
Section: Discussionmentioning
confidence: 99%